Biomarkers for the early detection of anthracycline-induced cardiotoxicity: current status - Horacek, Jan M; Vasatova, Martina; Pudil, Radek; Tichy, Milos; Zak, Pavel; Jakl, Martin; Jebavy, Ladislav; Maly, Jaroslav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2014)
BACKGROUND: Cardiotoxicity is a well-known and potentially serious complication of anticancer therapy. Anthracycline-based chemotherapy represents the greatest risk. Early detection of cardiotoxicity is crucial for applying preventive and supportive therapeutic strategies. METHODS AND RESULTS: Various methods have been recommended for monitoring of cardiotoxicity. In our conditions, echocardiography and electrocardiography are routinely used. However, this approach shows low sensitivity for the early prediction of cardiomyopathy when the possibilities of appropriate management could still improve the patient's outcome. Recently, biomarkers of cardiac injury have been investigated in the assessment of chemotherapy-induced cardiotoxicity. Cardiospecific biomarkers, such as cardiac troponins, show high diagnostic efficacy in the early subclinical phase of the disease before the clinical onset of cardiomyopathy. Increase in their concentrations correlates with disease severity. As for natriuretic peptides, some studies, including ours, have shown promising results. Definitive evidence of their diagnostic and prognostic role in this context is still lacking and natriuretic peptides have not been routinely used for monitoring of cardiotoxicity in clinical practice. Other perspective biomarkers of cardiotoxicity in oncology are under study, especially heart-type fatty acid-binding protein (H-FABP) and glycogen phosphorylase BB (GPBB). Our studies using GPBB have provided encouraging results. However, the available data are limited and their practical use in this context cannot be recommended until their clinical efficacy is clearly defined. CONCLUSIONS: This review covers the current status of biomarkers for the early detection of anthracycline-induced cardiotoxicity. The authors present in brief, their own experience with multiple biomarkers in the detection of cardiotoxicity.
Keywords: antracykliny; protinádorová antibiotika; Cardiotoxicity; Humans; Biomarkers; kardiotoxicita; Antibiotics, Antineoplastic; Anthracyclines; biologické markery; lidé